ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY DENGAN PENDEKATAN ACTIVE LEARNING DI KELAS XI MAN 1 MEDAN TP. 2018/2019 - Rizka Nurlina Damanik; Eka Khairani Hasibuan (State Islamic University of North Sumatra, 2019)
The problem in this study was the low interest in learning students to learn mathematics in students of class XI IPA MAN 1 Medan. This is evident from observations and interviews that researchers did. The results show a lack of understanding of students in learning mathematics so that more innovative teacher efforts and strategies are needed. The purpose of this study was to determine and analyze the ability of mathematical understanding of students of class XI MIA-2 MAN 1 Medan after the implementation of the Course Review Horay type of cooperative learning model. This research is a type of qualitative descriptive research and quantitative descriptive research, with a case study approach. The research subjects were XI MIA-2 MAN 1 Medan field class high, medium and low ability categories.